P1-S6.36 Cost-effectiveness of rapid tests to improve access to syphilis prevention among pregnant women in Peru. (10th July 2011) - Mallma, P; Carcamo, C; Valderrama, M; Chiappe, M; La Rosa, S; Garcia, P; Weaver, M; Holmes, K; Terris-Prestholt, F; Peeling, Rossana
Abstract : Background: Several recent articles compared the cost and cost-effectiveness syphilis testing strategies to avert congenital syphilis in settings with high syphilis prevalence. Current study contributes analysis in low-prevalence setting. Methods. Rapid syphilis testing (RST) was implemented at two different settings, both with syphilis prevalences of around 1%: (a) The Ventanilla-Network of outpatient clinics and a small hospital at a peripheral district in Peru, where the rapid syphilis test was implemented together with the rapid HIV testing (One finger stick, two tests"); (b) The National Maternal and Perinatal Institute (INMP) a tertiary hospital with a high number of patients, and Initially in both settings the only test available was RPR with low coverage. For the costing of RPR we included supplies, capital costs, human resources and costs associated to treatment. For the costing of RST, we included also start up costs (advocacy meetings with authorities, training, supervision, monitoring) and the cost of implementing a quality assurance system. Cost-effectiveness analyses compared the cost of screening and treatment for the joint program to the disability adjusted life-years saved when congenital syphilis was averted. Results: For the Ventanilla-Network the total cost was 5.98 for RST and 5.22 for RPR per woman screened and 580.83 and 1845.55 respectively per woman treated. In contrast, the total cost was 2.53 for rapid syphilis test and 3.15 for RPR per woman screened (the lower costs probably associated to the economy of scale, due to the large number of women seen at the INMP) and 336.80 and 1051.59 at INMP. At Ventanilla-Network, the cost per DALY saved from averting cases of congenital syphilis was 35.23 for rapid syphilis test and 111.95 for RPR. In incremental analysis, the rapid test was cost-saving. At INMP, the cost per DALY saved was 20.43 for rapid syphilis test and 63.79. For the Ventanilla-Network and the INMP the RST was cost-effective by the WHO standard of 64/DALY. Conclusion: Syphilis screening is cost-effective even in a low-prevalence setting. To the extent that HIV rapid tests are funded by PMTCT programs, the cost of scaling up rapid syphilis tests would be lower than these estimates, because the joint cost of blood sample collection would be borne by the PMTCT program.